The Political Antieconomy of Transformations in CEE Countries - Gylys, Povilas (Ekonomika, 2008)
Transformations in CEE countries traditionally are studied in the framework of methodological individualism. As a result, the scope of economic analysis is reduced to the development of the private sector. Thereby, part of economic reality, namely the public sector; is excluded from economic reality. The holistic approach allows to overcome this shortcoming. Holistically perceived transformations encompass the whole economy - both the private and the public sectors. Furthermore, it opens the possibility to widen the scope of investigations by introducing the negative side of transformations in economy as a whole. Conceptualization of this side allows formulating the concept of antieconomy. Introduction of this concept and the extension, development of the political economy tradition give the opportunity to speak about a new direction of scientific explorations - political antieconomy of trasformations.